2010
DOI: 10.2337/dc10-1393
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cardiovascular Disease Events in Patients With Type 2 Diabetes Prescribed the Glucagon-Like Peptide 1 (GLP-1) Receptor Agonist Exenatide Twice Daily or Other Glucose-Lowering Therapies

Abstract: OBJECTIVETo test the hypothesis that exenatide twice daily reduces the relative incidence of cardiovascular disease (CVD) events among patients with type 2 diabetes compared with other glucose-lowering agent(s).RESEARCH DESIGN AND METHODSA retrospective database analysis was performed of the LifeLink database of medical and pharmaceutical insurance claims for June 2005 through March 2009. Patients with no history in the preceding 9 months of myocardial infarction, ischemic stroke, or coronary revascularization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
167
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(178 citation statements)
references
References 21 publications
(33 reference statements)
6
167
3
2
Order By: Relevance
“…The available data do not indicate any increase in cardiovascular events with GLP-1 receptor agonists [89][90][91]. A meta-analysis of 36 trials with a duration ≥12 weeks showed that the MantelHaenszel OR (MH-OR) for major cardiovascular events versus placebo or other comparators was 0.74 for all GLP-1 receptor agonists (95% CI: 0.50-1.08, p = 0.12), 0.85 for exenatide (95% CI: 0.50-1.45, p = 0.55) and 0.69 for liraglutide (95% CI: 0.40-1.22, p = 0.20) [92].…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…The available data do not indicate any increase in cardiovascular events with GLP-1 receptor agonists [89][90][91]. A meta-analysis of 36 trials with a duration ≥12 weeks showed that the MantelHaenszel OR (MH-OR) for major cardiovascular events versus placebo or other comparators was 0.74 for all GLP-1 receptor agonists (95% CI: 0.50-1.08, p = 0.12), 0.85 for exenatide (95% CI: 0.50-1.45, p = 0.55) and 0.69 for liraglutide (95% CI: 0.40-1.22, p = 0.20) [92].…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…15 A number of clinical trials with GLP-1R agonists are ongoing where the effect on stroke is one of the outcome measures (see Table 1B). While most of these studies are performed in diabetic patients focusing on combined cardiovascular outcome measures, a few of them are directly focusing on stroke patients.…”
Section: The Glucagon-like Peptide-1 Receptormentioning
confidence: 99%
“…A few studies accounted for time-varying exposures by using Cox models analysing exposure to drugs as a timedependent variable [19,64,71,72,77,78]. These models make the assumption that treatment changes are independent of cardiovascular outcomes and may lead to biased results in the presence of patient characteristics that vary over time, affecting both diabetes treatment choice and cardiovascular risk [79], a likely scenario in the context of a chronic disease requiring therapy adjustments commensurate to its natural progression.…”
Section: Temporality Considerations In Administrative Databasesmentioning
confidence: 99%